Answers

2014-08-21T20:09:41+05:30
(x+y \sqrt{2})(3 -  \sqrt{2}) = -2 \\  \\ x + y \sqrt{2} = - \frac{2}{(3 -  \sqrt{2} )} \\  \\ x + y \sqrt{2} = - \frac{2(3 +  \sqrt{2} )}{(3 -  \sqrt{2} )(3 +  \sqrt{2} )} \\  \\ x + y \sqrt{2} = - \frac{6 + 2 \sqrt{2} }{5} \\  \\ x + y \sqrt{2} = - \frac{6}{5} - \frac{2}{5}  \sqrt{2} \\  \\ x = - \frac{6}{5} \\  \\ y = - \frac{2}{5} \\  \\ x - y = - \frac{4}{5} \\  \\ |x - y| =  \frac{4}{5}
0
questioners!! you should be habitual of picking best answers by choosing brainliest answer :P :P